Analysis of Motivation, Knowledge and Investment Education on Investment Interest in Capital Market - Kurniawan Patma; Maylen K.P. Kambuaya; Rama Soyan Arunglamba; Hesty T. Salle (Syntax Corporation Indonesia, 2021)
The purpose of this study is to determine and analyze the effect of investment motivation, investment knowledge on investment interest, investment education on investment interest in the capital market for students of the Faculty of Economics and Business, Cenderawasi University. The population taken in this study were students of the 2016 FEB Uncen Accounting Study Program and the 2017 class. The knowledge variable affected the investment interest of the 2016 FEB Uncen Accounting Study Program students and the 2017 class. Accounting FEB Uncen class 2016, class 2017 and class 2018.